Surface antigens on human melanoma cells studied with heterologous antisera - Roberts, G. P. (Nature Publishing Group, 1980)
Antisera were raised in rabbits to 6 human melanoma cell lines. The cell-surface antigens recognized by these antisera were examined using cell-surface labelling with (125)I, followed by immunoprecipitation of soluble extracts of the cells and polyacrylamide-gel electrophoresis of the immunoprecipitates in the presence of sodium dodecyl sulphate (SDS). Up to 16 cell-surface antigens were recognized by these antisera, and 5 of the melanoma cell lines had a similar profile of cell-surface antigens. Digestion of labelled melanoma cells with neuraminidase before immunoprecipitation revealed that 8 of the larger antigens were sialoglycoproteins. The melanoma antisera produced haemagglutination of human erythrocytes at high dilutions, but the antigens involved could not be detected by iodination. In contrast, absorption of the melanoma sera with lymphocytes and fibroblasts revealed that these cells did contain some cell-surface glycoproteins in common with melanoma cells. The melanoma antisera contained antibodies to foetal calf serum proteins, but the amounts of these proteins on the surface of melanoma-cells were very low. Immunoprecipitation of labelled melanoma cell extracts with monospecific antiserum to β(2)-microglobulin produced 2 bands with mol. wts corresponding to β(2)-microglobulin and the HLA-determinant polypeptide chain. After absorption of melanoma antisera with cross-linked foetal calf serum, erythrocytes, lymphocytes and fibroblasts, antibodies against 10 labelled antigens remained in the absorbed antisera. However, antibodies against 8 of these antigens were still detected after absorption of the melanoma antisera with melanoma cells. IMAGES: